2019
DOI: 10.1021/acs.nanolett.9b01666
|View full text |Cite
|
Sign up to set email alerts
|

L-Type Ligand-Assisted Acid-Free Synthesis of CsPbBr3 Nanocrystals with Near-Unity Photoluminescence Quantum Yield and High Stability

Abstract: X-type ligands, for example, the pair of oleylamine (OAm) and oleic acid (OA), have been widely used to prepare CsPbX3 nanocrystals (NCs). However, the proton exchange between coordinated OAm and OA may induce the detachment of ligands, resulting in poor performance after cleaning or long-time storage. Herein, density functional theory calculations predict that primary amines (L-type ligands) can stabilize a PbBr x -rich surface and yield a trap-free material with fully delocalized valence band maximum and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
217
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(226 citation statements)
references
References 54 publications
7
217
0
2
Order By: Relevance
“…However, the remained surface morphological defects and the presence of bulky alkylamine ligands hampered the carrier mobility, causing the recombination losses of photogenerated carriers, which remains unresolved. [ 31 ] The defects in perovskite is closely related to the trap‐states, and usually they act as the recombination centers. [ 32,33 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, the remained surface morphological defects and the presence of bulky alkylamine ligands hampered the carrier mobility, causing the recombination losses of photogenerated carriers, which remains unresolved. [ 31 ] The defects in perovskite is closely related to the trap‐states, and usually they act as the recombination centers. [ 32,33 ]…”
Section: Resultsmentioning
confidence: 99%
“…Then umber of vacancies or defects generated in the CsPbI 3 QD surface has been reported as aresult of the lower PLQY and lifetime. [40,41] Therefore,bydecreasing the density of surface trap states,w ew ere able to improve the optical properties of the L-PHE treated QDs.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…One pair of lone pair electrons of ammonia coordinates with Pb cations, leading to significantly passivation effect ( Figure a) . The X‐ray photoelectron spectroscopy (XPS) characterization is further performed to reveal the element state (Figure b,c).…”
Section: Resultsmentioning
confidence: 99%
“…For CsPbBr 3 QDs after ammonia treatment, one more peak at 399.05 eV can be detected, which can be assigned to N from NH 3. In the case of CsPbBr 3 QDs film, the interaction among Pb cations on the surface will decrease after ammonia removed, resulting in dynamic process of ammonia passivation of CsPbBr 3 QDs film. It is clearly concluded that the introduction of ammonia gas significantly enhances the optical performance of the material with structure retained through an ammonia‐lead coordination passivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation